The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1111/j.1365-2621.1964.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Mortem Changes in Physical and Chemical Properties of Bovine Musclea

Abstract: SUMMARY Post‐mortem changes in tenderness and protein solubility were studied in bovine semitendinosus muscles. Muscles excised immediately post‐mortem were compared with muscles left attached to the skeleton. Post‐mortem times of 0, 6, 12, 24, 72, and 312 hr were studied. Sarcoplasmic protein solubility was highest immediately after slaughter and lowest in muscles left attached to the skeleton. Myofibrillar protein solubility was decreased in muscles left attached. Protein solubility changed during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…However, reports on the effect of aging on cold-shortened meat are varied. Goll et al (1964), Herring et al (1967), and Bouton et al (1973) found that aging cold-shortened beef improved tenderness, whereas other studies found no improvement in tenderness as a result of aging (Davey et al, 1967;Locker, 1982). Locker (1982) suggested that the gap filaments (titin and nebulin) were the primary determinants of meat tenderness.…”
Section: Chilling Rate Effectsmentioning
confidence: 94%
“…However, reports on the effect of aging on cold-shortened meat are varied. Goll et al (1964), Herring et al (1967), and Bouton et al (1973) found that aging cold-shortened beef improved tenderness, whereas other studies found no improvement in tenderness as a result of aging (Davey et al, 1967;Locker, 1982). Locker (1982) suggested that the gap filaments (titin and nebulin) were the primary determinants of meat tenderness.…”
Section: Chilling Rate Effectsmentioning
confidence: 94%
“…Advancements in histological technology, including the electron microscope, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and western blotting, enabled further research in the area of postmortem muscle proteolysis (Bandman and Zdanis, 1988). Even though postmortem proteolysis presumably accounts for 30 to 40% of postmortem tenderization (Goll et al, 1997), most studies agree that proteolytic degradation has a minimal effect on muscle within the first 72 hours postmortem (Goll et al, 1964;Calkins and Seideman, 1988;Koohmaraie, 1994). Myofibrillar proteins maintain the structural integrity of myofibrils; thus, proteolysis of these proteins should result in loss of myofibrillar integrity and improved tenderness (Koohmaraie, 1996).…”
Section: Proteolysis Of Myofibrillar Proteinsmentioning
confidence: 99%
“…Shortly after Locker and Hagyard discovered the cold shortening effect in post-mortem bovine muscle, Goll et al, (1964) reported that post-mortem changes in tenderness of bovine muscle were very dependent on whether the muscle had been excised immediately after death or left attached to the skeleton. Thus, in muscle excised from the skeleton immediately after death, tenderness decreased during the first 6 to 48 hours post-mortem and then increased slowly.…”
Section: Umentioning
confidence: 99%